Carbon and nitrogen allocation and partitioning in traditional and modern wheat genotypes under pre‐industrial and future CO2 conditions. (3rd December 2014) - Aljazairi, S.; Arias, C.; Nogués, S.; Loreto, F.
Abstract The results of a simultaneous 13C and 15N labelling experiment with two different durum wheat cultivars, Blanqueta (a traditional wheat) and Sula (modern), are presented. Plants were grown from the seedling stage in three fully controllable plant growth chambers for one growing season and at three different CO2 levels (i.e. 260, 400 and 700 ppm). Short‐term isotopic labelling (ca. 3 days) was performed at the anthesis stage using 13CO2 supplied with the chamber air and 15NH4‐15NO3 applied with the nutrient solution, thereby making it possible to track the allocation and partitioning of 13C and 15N in the different plant organs. We found that photosynthesis was up‐regulated at pre‐industrial CO2 levels, whereas down‐regulation occurred under future CO2 conditions. 13C labelling revealed that at pre‐industrial CO2 carbon investment by plants was higher in shoots, whereas at future CO2 levels more C was invested in roots. Furthermore, the modern genotype invested more C in spikes than did the traditional genotype, which in turn invested more in non‐reproductive shoot tissue. 15N labelling revealed that the modern genotype was better adapted to assimilating N at higher CO2 levels, whereas the traditional genotype was able to assimilate N more efficiently at lower CO2 levels.